A method for inferring inequalities for probability values applied to complex networks. (5th September 2015) - Dehmer, Matthias; Shi, Yongtang
Abstract : In this article, we infer inequalities representing (upper) bounds for real quantities. The obtained bound is parametric and, hence, it might be applicable to special problems. Here, we apply it to probabilities assigned to complex networks. © 2015 Wiley Periodicals, Inc. Complexity 21: 113–115, 2016